2020
DOI: 10.3390/v12050512
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and Diverse Traits of Adhesion Devices from Siphoviridae Recognizing Proteinaceous or Saccharidic Receptors

Abstract: Bacteriophages can play beneficial roles in phage therapy and destruction of food pathogens. Conversely, they play negative roles as they infect bacteria involved in fermentation, resulting in serious industrial losses. Siphoviridae phages possess a long non-contractile tail and use a mechanism of infection whose first step is host recognition and binding. They have evolved adhesion devices at their tails’ distal end, tuned to recognize specific proteinaceous or saccharidic receptors on the host’s surface that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 96 publications
(199 reference statements)
4
67
0
Order By: Relevance
“…Tal (TMP+2) analysis yielded several hits ( Supplementary Figure 1 ). Contrary to most cases, the classical N-terminal structural domain found in all Tals ( Goulet et al, 2020 ) is identified by HHpred not at the N-terminus, but between residues 156 and 505 (PDB ID 3GS9, Listerial phage protein). Preceeding it, the domain comprised between amino-acids 1 and 155 in Vinitor162 is identified as Carbohydrate Binding Module 1 (CBM), a BppA (base plate protein) domain of lactococcal phage Tuc2009, a module widely spread in siphophages infecting Gram-positive hosts (PDB ID 5E7T, Legrand et al, 2016 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Tal (TMP+2) analysis yielded several hits ( Supplementary Figure 1 ). Contrary to most cases, the classical N-terminal structural domain found in all Tals ( Goulet et al, 2020 ) is identified by HHpred not at the N-terminus, but between residues 156 and 505 (PDB ID 3GS9, Listerial phage protein). Preceeding it, the domain comprised between amino-acids 1 and 155 in Vinitor162 is identified as Carbohydrate Binding Module 1 (CBM), a BppA (base plate protein) domain of lactococcal phage Tuc2009, a module widely spread in siphophages infecting Gram-positive hosts (PDB ID 5E7T, Legrand et al, 2016 ).…”
Section: Resultsmentioning
confidence: 96%
“…The structural components of the bacteriophage tail resembled the complex system found in a majority of characterized LAB phages, comprising a triad of proteins (gp16, tape measure protein, TMP; gp17, distal tail protein, Dit and gp18, tail associated protein, Tal) which allow the recognition and binding to host cell surface-located polysaccharides, or more rarely proteins ( Goulet et al, 2020 ). Gp16 was assigned to the TMP, which determines the length of the tail and participates in the infection mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking example of this is the conserved capsid fold across all members of the Caudovirales observed to date [38]. Other major structural proteins, like the major tail protein, the portal (connector) protein, and certain baseplate proteins are also highly conserved [46][47][48]. Presumably, this relatedness extends to scaffolding proteins as well; however, structural information on scaffolding proteins is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This phage has a genome size of 27,595 bp and 50 annotated open reading frames. Of interest here, phage p2 uses a multi-protein baseplate at the tip of its tail to bind to its cell wall polysaccharide (CWPS) receptor at the host cell surface [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present further structural analyzes of the phage p2 baseplate, proposing a topological model of the baseplate resting state, and interpreting a new nsEM structure of the virion, in its active conformation. These novel views on the activation mechanism of phage p2 may be applicable to other members of the Siphoviridae family exhibiting an activation mechanism [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%